The points at issue of the determination of «auxiliaries (dependent) nouns» term in Soviet and Russian Korean studies. - Lee., T. B. (Journal of Oriental Studies, 2016)
Linguists of the Soviet-Russian school of Korean Studies allocated the syntactic words in classification the parts of speech in Korean Grammar. But this concept doesn’t exist in modern Korean linguistic. The discrepancy of these classifications made that today there is the problem of definition and using the terms of some grammatical classes. This problem is connected with the class of nouns, which is called "auxiliaries nouns" in Russian Korean Studies. In this research we try to solve the question of the application of this term in a Soviet Korean Studies. Especially we recommend taking as basis not Soviet, but traditional Korean classification in process of teaching Korean grammar by Kazakh, which have the same grammatical structure with Korean.